Integrated microbial processes for biofuels and high value-added products: the way to improve the cost effectiveness of biofuel production - Silva, Teresa Lopes da (2014)
The production of microbial biofuels is currently under investigation, as they are alternative sources to fossil fuels, which are diminishing and their use has a negative impact on the environment. However, so far, biofuels derived from microbes are not economically competitive. One way to overcome this bottleneck is the use of microorganisms to transform substrates into biofuels and high value-added products, and simultaneously taking advantage of the various microbial biomass components to produce other products of interest, as an integrated process. In this way, it is possible to maximize the economic value of the whole process, with the desired reduction of the waste streams produced. It is expected that this integrated system makes the biofuel production economically sustainable and competitive in the near future. This review describes the investigation on integrated microbial processes (based on bacteria, yeast, and microalgal cultivations) that have been experimentally developed, highlighting the importance of this approach as a way to optimize microbial biofuel production process.